Mixed Small Cell Neuroendocrine Carcinoma and Conventional Acinar Adenocarcinoma of the Prostate: A Case Report. Issue 3 (May 2020) - Cordeiro-Rudnisky, Fernanda; Wu, Yubo; Sun, Yue
Abstract : Abstract: Prostate cancer with neuroendocrine (NE) differentiation can be classified into six categories: conventional adenocarcinoma with NE differentiation, adenocarcinoma with Paneth cell–like NE differentiation, carcinoid tumor, small cell carcinoma, large cell carcinoma, and mixed NE carcinoma-acinar adenocarcinoma. Mixed NE carcinoma-acinar carcinoma is a biphasic carcinoma characterized by the presence of NE (small or large cell) carcinoma and conventional acinar adenocarcinoma. In rare cases, these two components overlap without discrete classic small cell carcinoma or a usual prostate adenocarcinoma component, making it particularly difficult to determine whether these overlapping cases should be diagnosed as small cell carcinoma or adenocarcinoma with a high Gleason score. Here, we present the case of a 74-year-old man who was diagnosed with mixed small cell NE carcinoma and conventional acinar adenocarcinoma of the prostate.